1988
DOI: 10.1104/pp.86.4.1032
|View full text |Cite
|
Sign up to set email alerts
|

Gradients of Intercellular CO2 Levels Across the Leaf Mesophyll

Abstract: Most current photosynthesis models, and interpretations of many wholeleaf CO2 gas exchange measurements, are based on the often unstated assumption that the partial pressure of CO2 is nearly uniform throughout the airspaces of the leaf mesophyll. Here we present measurements of CO2 gradients across amphistomatous leaves allowed to assimilate CO2 through only one surface, thus simulating hypostomatous leaves. We studied five species: Eucalyptus pauciflora Sieb. ex Spreng., Brassica chinensis L., Gossypium hirsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
3

Year Published

1989
1989
2004
2004

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 7 publications
4
73
0
3
Order By: Relevance
“…Reiati\ely large A^,.^ differences were also found by Parkhurst et al (1988) using Mott & O'Leary's methods with twelve lea\'es of five species. When />" at the fed side was at normal atmospheric levels near 32 Pa, we found p^^ differences up to 2'3 Pa in Phaseolus vulgaris, 3 Pa in Brassica chinensis, 3-6 Pa in G. hirsutum, 3-7 Pa in Spinacia oleracea, and 7 3 Pa in Eucalyptus paucifiora.…”
Section: Empirical Evidencementioning
confidence: 98%
See 2 more Smart Citations
“…Reiati\ely large A^,.^ differences were also found by Parkhurst et al (1988) using Mott & O'Leary's methods with twelve lea\'es of five species. When />" at the fed side was at normal atmospheric levels near 32 Pa, we found p^^ differences up to 2'3 Pa in Phaseolus vulgaris, 3 Pa in Brassica chinensis, 3-6 Pa in G. hirsutum, 3-7 Pa in Spinacia oleracea, and 7 3 Pa in Eucalyptus paucifiora.…”
Section: Empirical Evidencementioning
confidence: 98%
“…For this reason, 'p^^'' will replace '/>,' in this paper (cf. Parkhurst et a/., 1988;Lloyd et al, 1992). Also, 'Pi,,.,' is the partial pressure at particular points within the intercellular airspace, and '?^' will represent the assimilation-weighted mean CO., pressure m the mesophyll, i.e.…”
Section: A Note About 'P'mentioning
confidence: 99%
See 1 more Smart Citation
“…Parkhurst et al (14) reported a relationship between rd, the diffusivity of CO2 in the air (Dd), and the thickness of the leaf (td). This relationship can be reduced to rd = 2td/Dd in hypostomatous leaves.…”
Section: Theorymentioning
confidence: 99%
“…To this aim we have carried out measurements of quantum yield, Chl fluorescence, CO2 and 02 responses of photosynthesis and have calculated 02 effects on photosynthesis. Changes in CO2 permeability inside the leaves were also considered since in schlerophyllous leaves the increase in leaf thickness could produce a substantial variation in the resistance to C02 diffusion (14).…”
mentioning
confidence: 99%